Effect of growth differentiation factor-9 and fibroblast growth factor-basic on small caprine oocyte development in vitro - GUPTA, P S P; SHREE, US PAVANNA; DHALI, A; NANDI, S (The Indian Journal of Animal Sciences, 2018)
The study aimed to assess the effect of growth differentiation factor-9 (GDF-9) and fibroblast growth factorbasic (bFGF) on in vitro development of small (